Effects of long-term training and competition on biochemical markers in elite female water polo players - Varamenti, E.; Platanou, T.; Kyparos, A.; Jamurtas, A. Z.; Koutedakis, Y.; Kouretas, D. (Serbian Journal of Sports Sciences, 2013)
Elite water polo athletes, in order to meet their goals and team expectations, undergo a heavy training and competition program throughout the year. The aim of this study was to identify and record the variations of the selected biochemical and hematological parameters related to health, injuries and performance in 14 elite female water polo players during the annual competition and training cycle. Venous blood was obtained in four distinct phases as follows: T1, preseason; T2, start of championship; T3, start of second round; and T4, playoffs. Data analysis revealed significant increases in hemoglobin (HGB) and hematocrit (HCT).